Giant Ovaric Cyst – a Rare Finding - Carvas, João M. (2019)
Serous cystadenomas are the main tumours of the ovarian epithelium in postmenopausal women. They can have a slow indolent growth, causing unspecific signs and symptoms, that are frequently not valued by the patients and by health professionals. This leads to a delay in the imaging exams and in the diagnosis. We present a clinical case of an giant abdominal cyst in a postmenopausal woman.